2021
DOI: 10.1002/jgh3.12658
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of nonalcoholic fatty liver disease in lean body mass population: A systematic review and meta‐analysis

Abstract: Author contribution: Shahinul Alam contributed to the conceptualization, methodology, writing-original draft, writing-review and editing, and supervision. Mohammad Jahid Hasan contributed to the methodology, investigation; data curation, writingoriginal draft, writing-review and editing, and project administration. Md Abdullah Saeed Khan contributed to the investigation, data curation, formal analysis, writing-original draft, and writingreview and editing. Mohammad Abdul Baker Chowdhury contributed to the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(446 reference statements)
0
12
0
Order By: Relevance
“…No significant differences were observed between these two groups with respect to diabetes prevalence, age, and levels of total cholesterol and low-density lipoprotein-cholesterol (LDL-C), suggesting that lean/ nonobese NAFLD patients may have a risk for developing metabolic diseases similar to NAFLD patients with obesity. Alam et al observed that lean and non-lean NAFLD patients had similar characteristics and shared common risk factors [35].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…No significant differences were observed between these two groups with respect to diabetes prevalence, age, and levels of total cholesterol and low-density lipoprotein-cholesterol (LDL-C), suggesting that lean/ nonobese NAFLD patients may have a risk for developing metabolic diseases similar to NAFLD patients with obesity. Alam et al observed that lean and non-lean NAFLD patients had similar characteristics and shared common risk factors [35].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Lean NAFLD subjects may have clinically similar metabolic dysfunction to obese or overweight individuals [ 45 ], even if they are at a much higher risk of developing metabolic dysfunction [ 46 ]. The pathogenesis of NAFLD in lean and obese individuals is not exclusively congruent.…”
Section: Discussionmentioning
confidence: 99%
“…Age is also an important risk of NAFLD in lean people. According to a meta-analysis, lean individuals with NAFLD were older than lean controls, with a mean difference of 2.87 years [ 21 ]. Sex differences have also been noted in NAFLD, such that a higher prevalence of NAFLD was found among males than among females.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some clinical parameters were not included in the present study, such as uric acid, HbA1C, C-reactive protein and homeostasis model assessment for insulin resistance (HOMA-IR). These parameters have been shown to be associated with lean NAFLD [ 21 , 33 ]. Third, we did not collect histological data from liver biopsies or other non-invasive imaging techniques, such as the controlled attenuation parameter measured by FibroScan ® or magnetic resonance imaging-derived proton density fat fraction to confirm the degree of the steatosis.…”
Section: Discussionmentioning
confidence: 99%